Dyslipidemic Diet-Induced Monocyte “Priming” and Dysfunction in Non-Human Primates Is Triggered by Elevated Plasma Cholesterol and Accompanied by Altered Histone Acetylation - Short, John D.; Tavakoli, Sina; Nguyen, Huynh Nga; Carrera, Ana; Farnen, Chelbee; Cox, Laura A.; Asmis, Reto (Frontiers in Immunology, 2017)
Monocytes and the recruitment of monocyte-derived macrophages into sites of inflammation play a key role in atherogenesis and other chronic inflammatory diseases linked to cardiometabolic syndrome and obesity. Previous studies from our group have shown that metabolic stress promotes monocyte priming, i.e. enhanced adhesion and accelerated chemotaxis of monocytes in response to chemokines, both in vitro and in dyslipidemic LDLR-/- mice. We also showed that metabolic stress-induced monocyte dysfunction is, at least to a large extent caused by the S-glutathionylation, inactivation, and subsequent degradation of MKP-1. Here, we analyzed the effects of a Western-style, dyslipidemic diet, which was composed of high levels of saturated fat, cholesterol, and simple sugars, on monocyte (dys)function in non-human primates (NHP). We found that similar to mice, a dyslipidemic diet enhances monocyte chemotaxis in NHP within four weeks, occurring concordantly with the onset of hypercholesterolemia but prior to changes in triglycerides, blood glucose, monocytosis or changes in monocyte subset composition. In addition, we identified transitory decreases in the acetylation of histone H3 at the lysine residues 18 and 23 in metabolically primed monocytes, and we found that monocyte priming was correlated with the acetylation of histone H3 at lysine 27 after an eight-week dyslipidemic diet regimen. Our data show that metabolic stress promotes monocyte priming and hyper-chemotactic responses in NHP. The histone modifications accompanying monocyte priming in primates suggest a reprogramming of the epigenetic landscape, which may lead to dysregulated responses and functionalities in macrophages derived from primed monocytes that are recruited to sites of inflammation